Uncovering student thinking about mathematics in the common core, grades 3-5 : 25 formative assessment probes - Tobey, Cheryl Rose.; Fagan, Emily R. (Thousand Oaks, California : Corwin, 2014)
This book helps pinpoint and reverse students' common math difficulties. Included are 20 research-based assessment probes designed specifically for Grades 3-5, to help teachers learn to ask the right questions to uncover just where students get confused, and apply practical strategies to get them quickly back on track.
Mathematic assessment probes -- Operations and algebraic thinking probes -- Number and operations: Base ten probes -- Number and operations: Fractions probes -- Measurement and data probes -- Geometry and geometric measurement probes -- Additional considerations -- Appendix A: Information on the standards for mathematical practice -- Appendix B: Developing assessment probes -- Appendix C: Action research reflection template: QUEST cycle.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Elementary) -- United States; Educational tests and measurements -- United States; Mathematics -- Study and teaching (Elementary) -- Psychological aspects; Mathematical ability in children -- United States -- Evaluation; Learning, Psychology of; Effective teaching -- United States